Dialog Nilai Mira Pakat Dayak Ma’anyan Di Banjarmasin Dengan Teks Filipi 2:1-7 : (Suatu Kajian Kultural Teologis) - Sudianto, Sudianto; Maleh, Kinurung; Ripaldi (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2024)
Mira Pakat is a noble value that is oriented towards unity of purpose and collective consciousness as Ma'anyan people. This value binds the Ma'anyan Dayak community as an identity and character of the Ma'anyan people. In the text of Philippians 2:1-7, the message to be like-minded, in one love, one soul, and one purpose is rooted in Jesus' example. The researcher conducted a dialogue on the values of Mira Pakat and the text of Philippians 2:1-7 with the Ma'anyan Dayak community in Banjarmasin. The research method used was qualitative research. Data was collected through interviews and observations. The results showed that the value of Mira Pakat is a noble value that must be maintained in the Ma'anyan Dayak community.